Radiological Manifestation of Neurological Complications in the Course of SARS-CoV-2 Infection - Sklinda, Katarzyna; Dorobek, Małgorzata; Wasilewski, Piotr G.; Dreżewski, Karol; Dȩbicka, Marta; Walecki, Jerzy; Mruk, Bartosz (Frontiers in Neurology, 2021)
Many reports suggest the SARS-CoV-2 infection may result in neurological complications. A wide spectrum of clinical syndromes have been reported, including both central and peripheral nervous system. Such symptoms may be a consequence of a direct viral injury, secondary to systemic inflammatory response, autoimmune processes, ischemic lesions or combination of these. Anosmia and dysgeusia are highly prevalent in the early stage of infection. Cerebrovascular events in patients with COVID-19 have also been documented with increasing frequency. Some cases of parainfectious autoimmune neurologic manifestations concurrent with active SARS-CoV-2 infection have been described, including hemorrhagic necrotizing encephalopathy, Guillain-Barré and Miller-Fisher syndromes. There are also a few reports documenting encephalitis and acute demyelinating encephalomyelitis (ADEM) in the course of COVID-19. There is also a growing number of cases of patients after recovery from COVID-19 with psychosomatic disorders, manifesting with memory disfunction, cognitive functions disorders, depression or other affective disorders, which may lead to a decrease of intellectual functions. Many of these neurological manifestations of the infection are possible to distinguish using radiological imaging techniques. It plays a very important role in evaluating the course of COVID-19 as well as diagnosing respiratory complications and choosing a proper management of infected patients. Similarly, radiological techniques play crucial role in identifying the cause of neurological symptoms connected to SARS-CoV-2 infection, being one of the most important elements of diagnostics. Especially in case of the presence of nervous system implication, using radiological imaging techniques to monitor the emerging onset of various symptoms is crucial to assess the severity and scope of involvement. Quick diagnostic process and identifying complications as fast as possible in order to implement specific treatment can be crucial to avoid long-term secondary conditions and accelerate the recovery period. In this review, we present the most important neurological complications that may occur in the course of SARS-CoV-2 infection and summarize their radiological manifestations.